(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The moral and aesthetic culture of a person is an important factor in the formation of the professional culture of managerial personnel, in the process of bringing their management skills, leadership abilities, knowledge, skills and experience into a single system that is inextricably linked with each other. The role of moral and aesthetic qualities in managerial activities is philosophically analyzed.